“The true-born Englishman” and the Irish bull: Daniel Defoe in the “Oxen of the Sun” episode of Ulysses - Davison, Sarah (Brill, 2016)
This essay uses evidence from the notes that Joyce made in preparation to recapitulate the historical development of English prose style in the “Oxen of the Sun” chapter of Ulysses to identify the traces of Defoe’s works that appear in the text of the Gabler edition. It investigates how Joyce used strategies of (mis)quotation and syntactical imitation to synthesise Defoe’s individual style and mobilise his authorial imprint, both as a stage in the recapitulation of the evolution of English prose and as a means to enact revenge on the narrative heritage of English imperialism. In doing so, it offers a genetic reinterpretation of Defoe’s presence in “Oxen” by the light of “Realism and Idealism in English Literature (Daniel Defoe–William Blake)”, Joyce’s notes for a series of lectures at the Università Popolare, Trieste (1912).